IDNLearn.com is committed to providing high-quality answers to your questions. Join our interactive Q&A community and get reliable, detailed answers from experienced professionals across a variety of topics.
Sagot :
Answer:
1) -3 is not equal to 3
2) -3
3) -183
4) 1112
5) 0
6) see explanation
7) positive
Step-by-step explanation:
1) "If a = − 9 and b = − 6, show that (a−b) ≠ (b−a)."
-9--6 -9+6= -3
-6--9 -6+9= 3
2) (-3) + (-7) = (-7) + ______
-3-7=-10 -10+7=-3
(-7)+ (-3) = -10
3) Subtract − 134 from the sum of 38 and − 87.
38+-87
38-87=-49
-49-134= -183
4) Find the product of: 16 x (-36) + (-36) x -46
16×-34= -544
-36×-46= 1656
-544+1656= 1112
5) "Find each of the following products:i) (-12) x 0 x (-56) ii) (-654) x 1
times zero is in the equation so it equals 0
6) "Verify a – (-b) = a + b for the following values of a and b.i) a = 15, b = 9
15-(-9)=
15+9=24
two negatives make a positive
5+9=24
24=24
7) What will be the sign of the product, if we multiply 90 negative integers and 9 positive integers?
positive, 90 is divisible by two so all of those cancel out into a positive and then a positive times a positive is positive
Thank you for being part of this discussion. Keep exploring, asking questions, and sharing your insights with the community. Together, we can find the best solutions. Thank you for visiting IDNLearn.com. We’re here to provide dependable answers, so visit us again soon.